Development and validation of an HPLC method for the simultaneous determination of amlodipine, hydrochlorothiazide, and Valsartan in tablets of their novel triple combination and binary pharmaceutical associations - Vignaduzzo, Silvana Edit (2011)
The novel triple combination between Amlodipine (AML), Hydrochlorothiazide (HCT), and Valsartan (VAL) provides a new option for treating hypertension. The development and validation of an HPLC method for their simultaneous determination in pharmaceutical combinations, employing experimental design strategies, is reported. The drugs were separated on a C18 column at 30° C, using a 38:62 (v/v) mixture of 30 mMphosphate buffer (pH 5.5) and MeOH as mobile phase, delivered at 1.0mLmin -1. Detection was performed at 234 nm. Despite the wide difference in analytes' concentrations, the method showed good linearity (r 2 > 0.995) in the ranges 7.0-13.0 μg mL -1, 17.6-32.8 μg mL -1, and 226.2-420.2 μg mL -1 for AML, HCT, and VAL, respectively, being specific (peak purity > 0.999), accurate (bias ofanalyte recoveries <2.0%), and precise (inter-and intra-day variations <2%). It was also robust to small changes inflow rate (±0.05 mL min -1), pH (±0.1 unit) and proportion of MeOH (±3%) in the mobile phase. The method was applied to the assay of AML, HCT, and VAL in tablets of their novel association and formulations containing the HCT-VAL and AML-VAL binary combinations. Copyright © Taylor & Francis Group, LLC.